2018
DOI: 10.7150/thno.26370
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biodistribution analysis across four different 89Zr-monoclonal antibody tracers—The first step towards an imaging warehouse

Abstract: Rationale: Knowledge on monoclonal antibody biodistribution in healthy tissues in humans can support clinical drug development. Molecular imaging with positron emission tomography (PET) can yield information in this setting. However, recent imaging studies have analyzed the behavior of single antibodies only, neglecting comparison across different antibodies.Methods: We compared the distribution of four 89Zr-labeled antibodies in healthy tissue in a retrospective analysis based on the recently published harmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 41 publications
4
38
0
Order By: Relevance
“…In a study exploring the biodistribution of four therapeutic antibodies (lumretuzumab, MMOT0530A, bevacizumab, and trastuzumab) labeled by radioactive 89 Zr, Bensch et al found that an estimated total amount of tracer accumulated in fat tissue ranged between 1.56% and 18.95% of the injected dose, depending on the physique of the patient. 27 A similar biodistribution was found for the four antibodies, probably because of their similar molecular structure, binding characteristics, and catabolic pathways. 27 Hence, despite low accumulation per gram of tissue, fat can influence the overall distribution of therapeutic antibodies.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In a study exploring the biodistribution of four therapeutic antibodies (lumretuzumab, MMOT0530A, bevacizumab, and trastuzumab) labeled by radioactive 89 Zr, Bensch et al found that an estimated total amount of tracer accumulated in fat tissue ranged between 1.56% and 18.95% of the injected dose, depending on the physique of the patient. 27 A similar biodistribution was found for the four antibodies, probably because of their similar molecular structure, binding characteristics, and catabolic pathways. 27 Hence, despite low accumulation per gram of tissue, fat can influence the overall distribution of therapeutic antibodies.…”
Section: Discussionmentioning
confidence: 64%
“…27 A similar biodistribution was found for the four antibodies, probably because of their similar molecular structure, binding characteristics, and catabolic pathways. 27 Hence, despite low accumulation per gram of tissue, fat can influence the overall distribution of therapeutic antibodies. 27 This "storage effect" of the adipose tissue may contribute to our results.…”
Section: Discussionmentioning
confidence: 64%
“…Thanks to its nuclear characteristics (t 1/2 =78.41 h, 22.3% positron emission with a maximum decay energy of 900 keV), zirconium-89 ( 89 Zr) is a very promising radionuclide for immuno-PET (positron emission tomography using an antibody to target the cells of interest) [1][2][3][4][5]. It can also be used for bio distribution studies of labelled monoclonal antibodies [6]; furthermore, in literature it was reported a method to prepare pharmaceuticals for simultaneous magnetic resonance imaging and PET [7].…”
Section: Introductionmentioning
confidence: 99%
“…Given this caveat, we cautiously interpret our findings and encourage replication studies and those that examine VEGF-A levels in the brains of ASD patients in vivo . For example, the anti-VEGF antibody bevacizumab has been radiolabeled with zirconium-89 ( 89 Zr-bevacizumab) and used in clinical applications, showing some uptake into the brain [69,70]. However, the utility of 89 Zr-bevacizumab as an imaging marker capable of detecting modest changes in VEGF-A levels in the central nervous system is yet to be demonstrated.…”
Section: Resultsmentioning
confidence: 99%